Penerapan Model Pembelajaran Inkuiri Terbimbing pada Materi Sistem Ekskresi Kulit untuk Meningkatkan Keterampilan Proses Sains Siswa Kelas XI SMA - Purwati, Rani; Prayitno, Baskoro Adi; Sari, Dewi Puspita (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
Science Process Skill (SPS) on the biology learning can facilitate student to reach the science learning and push student to find their own concept of knowladge, facs along with develop attitude and values. The purpose of this research is to improve student’s at class XI IPA 2 of SMA in skin excretory system using guided inquiry. Participan in this reasearc is 36 student of class XI SMA in Karanganyar who choose sciene program. The target of this research is to increase percentage of each skill indicator on SPS about ≥10%. The result of this research shows an the  average percentage on student’s SPS increasing from 29,78% to 65,34%. But, in the classification skill need to be trained more intensively, because it has not reached the target. Based on the result above the conclusion that guided inquiry can improvement student’s SPS participan.Keywords:        guided inquiry model, science process skill, skin excretory system